Brazilian Dry Forest (Caatinga) Response To Multiple ENSO: the role of Atlantic and Pacific Ocean - Pereira, Marcos Paulo Santos; Mendes, Keila Rego; Justino, Flavio; Couto, Fabiana; da Silva, Alex Santos; da Silva, Djane Fonseca; Malhado, Ana Claudia Mendes (The Science of the total environment, 2020)
The semi-arid region of Northeast Brazil (NEB) experiences severe droughts during El Niño Southern Oscillation (ENSO) years, with major impacts on the dynamics of the native vegetation (Caatinga). However, the effect of these droughts on carbon cycling is not well understood. Here, a numerical model is used to investigate the influence of variations in Pacific and Atlantic sea surface temperatures (SST) on drought and carbon dynamics of the Caatinga during past ENSO events. We demonstrate that precipitation reductions in the Caatinga have a strong influence on vegetation dynamics, with net primary production (NPP) remaining low throughout the droughts. Furthermore, the Caatinga acts as a carbon sink, even in years of severe drought. However, net ecosystem exchange (NEE) is lower in years of low NPP rates, resulting in long periods with limited ecosystem activity. The SST patterns indicate that extreme vegetation changes in the Caatinga are associated with the combination of ENSO events and North Atlantic SST warming. [Display omitted] •Caatinga acts as a carbon sink even in years of severe drought.•Climatic extremes are key factors in Caatinga contribution to Global Carbon Balance.•ENSO events combined with North Atlantic SST warming causes extreme Caatinga changes.